Respon Pertumbuhan Bibit Lada (Piper nigrum l.) Terhadap Komposisi Media Tanam dan Konsentrasi Pupuk Organik Cair - Syam, Netty (Journal Galung Tropika, 2020)
Availability of pepper seeds continuously, good quality, and free from stem rot disease is still limited at the farmer level. This study aims to determine the composition of the planting medium and the best concentration of organic fertilizers in spurring pepper seeds’ growth. The study was compiled using a two-factor factorial design based on a randomized block design. The first factor is the media’s composition for planting sand, compost, and soil in 5 levels, namely 1:0:1, 1:1:0, 1:1:1, 1:2:1, and 2:1:1. The second factor is applying liquid organic fertilizer (POC), made from forage. It consists of three levels of concentration, namely POC 10 ml, 20 ml, and without POC (control). Fifteen treatment combinations were repeated three times. The results showed that the combination of POC and the composition of the planting medium could stimulate pepper seedlings’ growth. POC 20 ml/liter and the composition of the media of sand + compost + soil 1:1:0 and 1:1:1 resulted in the best shoot lengths, namely 13.91 cm and 13.23 cm, respectively. The planting medium of sand + compost + soil with a composition of 1:1:1 was able to spur the emergence time of pepper cuttings faster, namely 19.13 days after planting, and the number of leaves was higher, namely 5.40.